Assessing daily life activities with experience sampling methodology (ESM): Scoring predefined categories or qualitative analysis of open-ended responses? - Marie Stadel; Anna M. Langener; Katie Hoemann; Laura F. Bringmann (Methods in Psychology)
One domain frequently assessed in Experience Sampling Methodology (ESM) studies is that of daily activities. This is often done with predefined (and unvalidated) categorical items, but can also be done using open-ended items. ESM researchers, however, lack tools and guidance in analyzing the obtained open-ended data. In the first part of this paper, we use data from a 28-day ESM study in which students reported their activities both categorically and open-endedly to compare these two assessment approaches. We additionally present participant preferences and reflections captured in exit interviews. In the second part, we illustrate the qualitative analysis process for open-ended ESM responses. All code and tools we used (including a newly developed Shiny App facilitating the coding of responses to open-ended ESM items) are shared for use in future research. Our results highlight the advantages and limitations of both assessment approaches: while categorical items offer simplicity, they often lack specificity. Conversely, open-ended responses provide richer, more personalized data, making them particularly valuable in idiographic clinical applications and exploratory research. A combination of both formats may enable the most effective assessment. We hope the tools we provide encourage the further use and exploration of open-ended ESM assessments.